NATIONAL-CULTURAL SEMANTICS OF PHRASEOLOGY: AN EXPLORATION INTO THE HEART OF IDIOMS AND EXPRESSIONS (Scientific journal of the Fergana State University, 2024)
The phraseological units are the anchors of a nation's cultural, historical, and social roots, offering invaluable insights into its unique ethos and evolution. This article ventures into the rich landscape of national-cultural semantics intrinsic to phraseology. By dissecting idioms and expressions, we unravel the intricacies of cultural narratives, the shadows of historical events, and the silent proclamations of societal values that collectively craft the linguistic identity of nations.